2019
DOI: 10.1108/hff-08-2018-0450
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field analysis and cooling system design for high power switched reluctance motor

Abstract: Purpose The electromagnetic field and cooling system of a high power switched reluctance motor (SRM) are studied numerically. The geometry of the motor and its main components are established using a computer-aided design software in the actual size. This study aims to evaluate the resulting thermal losses using the electromagnetic analysis of the motor. Design/methodology/approach In the electromagnetic analysis, the Joule’s loss in the copper wires of the coil windings and the iron losses (the eddy current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Husain et al [43] found that a single U-shaped arrangement of permanent magnets was more effective in cooling the rotor. For improving the convection transfer efficiency of a stator and rotor, Yan et al [44] added a fan to the main shaft and enlarged the grille area, as illustrated in Figure 13. For convective heat transfer in the motor gap, improving the gas flow state in the gap is a very important parameter, which is affected by the flow rate, gap size, etc.…”
Section: Air Gap Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Husain et al [43] found that a single U-shaped arrangement of permanent magnets was more effective in cooling the rotor. For improving the convection transfer efficiency of a stator and rotor, Yan et al [44] added a fan to the main shaft and enlarged the grille area, as illustrated in Figure 13. For convective heat transfer in the motor gap, improving the gas flow state in the gap is a very important parameter, which is affected by the flow rate, gap size, etc.…”
Section: Air Gap Convectionmentioning
confidence: 99%
“…Husain et al [43] found that a single U-shaped arrangement of permanent magnets was more effective in cooling the rotor. For improving the convection transfer efficiency of a stator and rotor, Yan et al [44] added a fan to the main shaft and enlarged the grille area, as illustrated in Figure 13.…”
Section: Air Gap Convectionmentioning
confidence: 99%
“…In addition, research has also pointed out the impact of surface modification on two-phase immersion cooling technology. Surface modification technology can further enhance phase change heat transfer in the cooling system and improve the thermal conductivity efficiency of the system [13]. Meanwhile, studies on the heat transfer characteristics of natural and forced convection have also shown that these systems perform well in single-phase immersion cooling applications in data centers.…”
Section: Variable Capacity Systems and Energy Efficiencymentioning
confidence: 99%
“…Rated Speed = 5300 rpm Rated Torque = 70 Nm Yan et al 10 (2019) Type = SRM Hybrid cooling system of both air-cooled and liquid-cooled system A maximum coil winding temperature drop of 17.7% was obtained for the liquid flow of Reynolds number (Re) = 500. The higher liquid flow rate of Re = 1500 was also used, whereas the air cooling was only helpful when the motor speed was higher than 4000 rpm.…”
Section: Power = 40 Kwmentioning
confidence: 99%